Design, synthesis and biological evaluation of novel hydroxy-phenyl-1H-benzimidazoles as radical scavengers and UV-protective agents. (1st January 2017) - Bino, Alessia; Baldisserotto, Anna; Scalambra, Emanuela; Dissette, Valeria; Vedaldi, Daniela Ester; Salvador, Alessia; Durini, Elisa; Manfredini, Stefano; Vertuani, Silvia
Abstract: An ever-increasing incidence of skin neoplastic diseases is registered. Therefore, it is important to protect the skin from the UV radiation that reaches the epidermis and dermis but also to block ROS generated by them. Our attention was attracted in developing new compounds provided with both UV filtering and antioxidant capacities. To this end, 2-phenyl-1H-benzimidazole-5-sulfonic acid (PBSA), a known UV filter, was selected as lead compound for its lack of antioxidant activity, high water solubility and good safety profile. PBSA was sequentially modified introducing hydroxyls on the phenyl ring and also substituting the functional group in position 5 of the benzimidazole ring. At the end of the synthetic study, a new, very potent class of antioxidants has been obtained. Surprisingly some of the developed molecules, while devoid of significant UV-filtering activity was endowed with potent UV-filtering booster capability if associated with known commercial UVB and UVA filters.